Diagnosis and approach to glucocorticoid-induced adrenal insufficiency and glucocorticoid withdrawal syndrome - Aleksandra Kiełczewska; Grzegorz Szcześniak; Anna Kiełczewska (Kazimierz Wielki University, 2024)
Introduction and purpose: Primary adrenal insufficiency can result from diseases affecting the adrenal glands, while secondary adrenal insufficiency is caused by suppression of the hypothalamic-pituitary-adrenal axis. The most common cause of adrenal suppression is exogenous steroids, a condition recently termed glucocorticoid-induced adrenal insufficiency (GIAI). Glucocorticoid-induced adrenal suppression is a common adverse effect of glucocorticoid therapy, which can have severe consequences. This review provides a comprehensive overview of the diagnosis and management of glucocorticoid-induced adrenal insufficiency and glucocorticoid withdrawal syndrome. Material and methods: An extensive examination of articles published in scientific journals was carried out through online research  platforms PubMed and Google Scholar.  We searched articles by entering keywords in appropriate configuration: "glucocorticoid-induced adrenal insufficiency", "glucocorticoids", "steroids", "adrenal crisis", "substitution therapy", "glucocorticoid withdrawal". Description of the state of knowledge: Glucocorticoids are widely used in the treatment of various inflammatory and autoimmune disorders due to their potent anti-inflammatory and immunosuppressive effects. However, chronic glucocorticoid therapy can lead to a number of adverse effects, including adrenal suppression, which can result in adrenal insufficiency. Summary: Primary care clinicians should recognize the high prevalence of glucocorticoid-induced adrenal insufficiency in patients receiving non-oral glucocorticoid formulations. The glucocorticoid withdrawal syndrome exhibits symptoms analogous to glucocorticoid-induced adrenal insufficiency. Additional data on the morbidity and mortality linked to glucocorticoid-induced adrenal insufficiency is needed to comprehend the associated health risks, which will ultimately guide the approach to care for patients tapering long-term glucocorticoid therapy.